The Influence of Hypnotherapy on the Coaching Achievement of Athletes in the Sports Branch of Jump and Throw Numbers - Amirzan Amirzan; Indra Kasih (Journal Physical Education, Health and Recreation, 2020)
This research used experimental design in the form of one group pre-post design, aimed to find out; the effect of hypnotherapy on fostering athletes' achievements in jump and throw sports. The population was all athletes in the athletic sport of jumping and throwing of 23 people. The technique of determining the sample by positive sampling, while the technique of data analysis used descriptive frequency analysis and paired sample test analysis (paired t-test) through the SPSS program version 20.00 at a significant level α = 0.05. The results showed that "the influence of hypnotherapy on fostering athlete achievements in jump and throw sports, t-test values of t-count of 2,354 and t-table (22; 0.05) of 1,717 with a significant level of 0.028 (0.028 < α = 0.05) or (t_count> t_table) The conclusion of this study was there is an influence of hypnotherapy on fostering athlete’s achievement suggestibility (tance level test) in jump and throw of athletic sports.